Memristor Effect in Layered Film Structures - V. T. Pham; D. A. Podryabinkin; E. B. Chubenko; V. E. Borisenko (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2024)
Equivalent  electrical  circuits  of  multilayer  film  structures  with  memristor  switching  of  resistance at   interlayer boundaries and at the boundaries of crystal grains in each layer are proposed. Numerical modeling of   the  current-voltage characteristics of such structures has shown that their loop-shaped form, typical of memristors, is transformed into a linear ohmic dependence of the total current on the magnitude of the applied external voltage as both the number of layers and the number of grains in each layer increase. A certain combination of the  number of layers and grains in a layer has been established, at which the maximum total current flowing through the structure and the ratio of resistances in the “off” and “on” states reach the highest values.